DENTAL PROSTHESES AND TOOTH-RELATED FACTORS IN PERIODONTITIS. A NARRATIVE REVIEW - Odette Luca; George-Alexandru Maftei; Liliana Pasarin; Ilinca Luca; Ruxandra Stan; Monica Tatarciuc; Ioana Martu (Romanian Dental Association for Education, 2022)
This narrative review summarizes the current evidence about the role that the fabrication and presence of dental prostheses and tooth-related factors have on the initiation and progression of gingivitis and periodontitis. Tooth anatomic factors, such as root abnormalities and fractures, and tooth relationships in the dental arch and with the opposing dentition can enhance plaque retention. Tooth-supported and/or tooth-retained restorations and their design, fabrication, delivery, and materials have often been associated with plaque retention and loss of attachment. Hypersensitivity reactions can occur to dental materials. Placement of restoration margins within the junctional epithelium and supracrestal connective tissue attachment can be associated with gingival inflammation and, potentially, recession. Restoration margins located within the gingival sulcus do not cause gingivitis if patients are compliant with self-performed plaque control and periodic maintenance. The presence of fixed prostheses finish lines within the gingival sulcus or the wearing of partial, removable dental prostheses does not cause gingivitis if patients are compliant with self-performed plaque control and periodic maintenance.